Methods of failure diagnostics of tantalum oxide-semiconductor capacitors with solid dielectric - Nevludov, I. Sh.; Gurin, V.; Gurin, D. (ХНУРЕ, 2018)
The subject of the study is oxide-semiconductor capacitors, which are widely used in the manufacture of electronic equipment. The goal of the study is to determine the main causes of failures of oxide-semiconductor capacitors at the production and operation stages. For this purpose, analogs of flat film capacitors have been built, which represented various production and operational situations (including dielectric breakdown); the structures of individual layers of capacitors, their chemical and phase formulas and electrical properties were found. Since capacitor anodes have a porous structure and are not subjected to the usual methods of studying flat objects, we used the simulation method. The simulated data were compared with the corresponding values measured on capacitors that did not work during operation or testing. In the process of research, the following tasks were solved: physical phenomena occurring in capacitors under the influence of various factors appearing in the production process were considered. It is shown that redox processes lead to deterioration of the capacitors. It is established that the main causes of the degradation of capacitors are thermodynamic in nature and they reduce the lifetime of the capacitors. Technological operations have been developed that significantly reduce or eliminate the types of failures considered. These include the basic operations of the process. Doping of the anodes of the capacitors with nitrogen. This operation is performed simultaneously with the sintering of porous anodes and contributes to the increase of the lifetime, operating temperatures and reverse voltage of the capacitors. Growing a multilayer dielectric by cyclically changing the formula of the electrolyte, where anodizing occurs. Formation of a dense cathode by applying an alternative electric field when impregnating porous anodes. Organic silicon impregnation of capacitors’ sections. This creates a dense waterproof film that blocks areas of free dielectric contact with manganese dioxide and provides good adhesion of the protective organic film to the section. The following methods were used in the work: electron beam probing, Auger spectroscopy and microprobe measurements.
Keywords: oxide-semiconductor capacitor; simulation method; failure analysis